IDENTIFIKASI PROKASTINASI AKADEMIK MAHASISWA DENGAN MEMBANGUN KESADARAN DIRI MELALUI KONSELING ISLAMI - Sulthon, Sulthon; Munir, Muhammad Misbahul (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2024)
Procastination is a habit that is often carried out by final year students and is detrimental to academics. This research aims to: 1) knowing the causes of academic procastination of final year students; 2) know how to overcome academic procastination in final year students by building self-awareness through Islamic counseling. The method used in this research is field research with a qualitative approach, data collection techniques using interviews, observation and documentation. Data analysis uses data display, data reduction and clarification steps. The research results show that;1) Factors that trigger academic procrastination in final year students are personality factors, namely self-interest and motivation, self-order, self-efficacy, low self-control, fear of failure, unimportant activities, lack of communication with supervisors, and cultural factors: 2) How to overcome the occurrence of student academic procastination with Islamic counseling, namely:(1) building self-awareness through 7 steps, namely repentance, wara', asceticism, qona'ah, gratitude, patience and sincerity;(2) strengthening aspects of student personality,(3) build good communication with the final assignment supervisor,(4) control the progress of the final assignment as feedback, provide humanist guidance, and strengthen awareness.